Adoção intuito personae: a vida social em confronto com a lei - Barbosa, Ana Paula da Silva (2013)
Is it legitimate for a family, willing to give up a child for adoption, to choose to whom it will give the infant? Why is this way of adoption, known as intuito personae, still predominant in the Brazilian adoptions? It occurs in prejudice of the process developed by the Cadastres in the Infancy and Youth Warders, as indicated in studies by Gueiros (2007) and Mariano & Rossetti-Ferreira (2008). Thesequestions oriented the beginning of this study. With the goal of subsidizing the discussion on the millenary voluntary cession of children, under the light of different historical, political and cultural determinants, we initially built the theoretical construction of the conceptual basis of family, infancy, relationships of gender and of maternity. It was deemed necessary the use of the concept of ―children circulation‖, borrowed from Anthropology, for the understanding of the historical rescue done from the Portuguese instrument ―Wheel of the Exposed‖ and its legacy to Brazil. The theme of adoption was reflected while one of the countless ways of public-private confronting in Brazil for situations in which the parents cannot offer care to their children. For that, this reflection is done within the due comprehension of the reality of the inequalities in the Country. In order to comprehend the current dilemmas, false or real, the intuito personae adoption, we point out the possible benefits and prejudices of the―ultra judiciarization‖ of adoption facing the current legislation, of the ECA and of the alterations of the new law 12.010/2009. Before the complex and intriguing theme investigated, we find a fertile ground for analysis and debate of ―success‖ and ―lack of success‖ of the adoptions, with direct and indirect indicators, constructed after consultations with professionals of Social Service and Psychology, active in the area. The subsequent field work is made of the comparative analysis of adoption cases from the Adoption Cadastre, and from the intuito personae, occurred for more than fifteen years in the Infancy and Youth Warder, with parents and respective adopted children. Semi-structured interviews with the subjects were used as the main instrument of data collection. The conduction of the research was possible with four adopted families, being one constituted by adoption of the Cadastre. Important divergent points were found between the two adoption types of adoption: in the intuito personae, the presence of the open adoption, better level of information on the biological origins, fear of losing the child to the mother and a lesser degree of planning of the adoption project. In the case of the adoption by Cadastre, we observe the closed adoption, better planning of the adoption and fear of losing the child directed to the Judiciary (represented by the figure of the Judge and the officials of the Infancy Warder)